Cáncer de cuello uterino : más allá de lo que es; la percepción de las mujeres de Antioquia (Colombia) y Colima (México), 2008 (2009)
ABSTRACT: To describe and interpret women’s perceptions about cervical cancer, its causes, prevention and self care. Methodology: qualitative studie, through the discussion group, 22 groups were formed in three municipalities in Antioquia (Colombia) and one municipality of Colima (Mexico), with 108 women. Results: descriptions and interpretations are collectively influenced by information from the health sector, the media and the family. Most women are not related cervical cancer or cervical infections with sexual and reproductive behavior. The acceptance of the Pap smear is a product of experience and responsibility. Conclusions: equity in access considers cultural differences and specific needs of women, breaking cultural barriers and opens up opportunities for participation in health services. In body care, women recognize the level of severity of signs and gynecoobstetrical symptoms and the need for medical care. There is little knowledge about cervical cancer, its causes and prevention, due to lack of information and education from health care providers.